A Decolonial Reading of Ronnie Govender's "Over My Dead Body". Issue 3 (2nd July 2020) - Chetty, Rajendra
Summary: This article discusses the contribution of Ronnie Govender, a South African writer, to build decolonial sensibilities and delink from the grand narrative of the colonial literary landscape in the short story "Over My Dead Body". Govender uses the world of art to make a decolonial statement. Decolonial artists work in the entanglement of power and engage with a border epistemology, those in the margins, the wretched of the earth. "Over My Dead Body" foregrounds the wounds infringed by racism, a pillar of Eurocentric knowing, sensing and believing that sustains a structure of knowledge. This structure is embedded in characters, institutions and languages that regulate and manage the world of the excluded. Healing is the process of delinking, or regaining pride, dignity, and humanity. The legacies of the community of Cato Manor that was pushed out of their land are built in Govender's stories. Decoloniality then is a concept that carries the experience of liberation struggles and recognises the strenuous conditions of marginalised people together with their strength, wisdom, and endurance. The body invoked by decolonial thinkers like Fanon and Biko is a black body, a racialised and humiliated body.